Changes in the legal regulation of criminal proceedings under martial law (Law and Safety, 2023)
Russia’s full-scale war against Ukraine has caused changes in the everyday life of Ukrainians, as well as in the functioning of state bodies and institutions. This has led to relevant amendments and additions to a number of legal acts, including criminal procedure legislation. The rules governing pre-trial investigation and court proceedings under martial law have also been amended. However, the analysis of the Criminal Procedure Code of Ukraine shows that some of the innovations are generally positive, but certain aspects of legal regulation may raise doubts and concerns, and are quite controversial and controversial.Under the new rules of pre-trial investigation, investigators and prosecutors can reduce the role of defence counsel, and are allowed not to involve them in all stages of the process or to do so via audio and video conferencing. However, this practice may limit the ability of defence counsel to perform their duties, as they will not be able to be at the scene and will not be able to effectively defend their client at all stages of the investigation. Under the proposed amendments, the prosecutor will receive powers that previously belonged only to the investigating judge, if circumstances make it impossible for the latter to perform his or her duties. However, the law does not provide a clear list of such situations, so the prosecutor will decide whether the investigating judge can perform his or her functions. This leads to a lack of judicial control over the observance of human and civil rights and freedoms and puts the defence at a disadvantageIn addition, such amendments directly violate Article 124 of the Constitution of Ukraine, which prohibits the delegation of court functions and their appropriation by other bodies or officials.The investigator and prosecutor may obtain evidence of a person's guilt, which may contradict his or her rights and freedoms. Nevertheless, the court has no right to disregard such evidence, which may lead to possible abuse by the investigator and prosecutor, which may result in human rights violations and unfair sentences.The heads of the prosecutor's office and pre-trial investigation bodies are entitled to seize the property of suspects or accused persons without a trial. However, if the criminal proceedings are subsequently closed or the person is found not guilty, the law does not require the return of such property or compensation for its value. This can lead to mass deprivation of property without the possibility of return.In this context, there is a need to eliminate legislative conflicts for effective and unambiguous practical implementation of legislative provisions for the purpose of investigating criminal proceedings under martial law.
Keywords: criminal proceedings; investigative (“detective”) actions; detention; martial law; Russian aggression.